Energy flux of electromagnetic field in stochastic model of radiative heat transfer in dielectric solid medium - Virchenko, Yu.P.; Lam Tan Phat (Functional Materials, 2017)
The stochastic model that describes radiative heat transfer in dielectric medium is analyzed. The model is based on the representation that heat transfer is realized both by its heat conductivity and by electromagnetic radiation that is generated by thermal fluctuations in the medium. Such physical suppositions, using fluctuation-dissipative theorem, are realized in the form of the infinite dimensional Ornstein-Uhlenbeck process that describes medium fluctuations. In the model frameworks, the energy flux density of fluctuating electromagnetic field is calculated in the form of a functional of the temperature distribution in real three-dimensional media sample.